(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides an academic analysis of the plot construction in Abdulla Qodiriy’s novel Bygone Days (O‘tkan kunlar), focusing on its structural logic, aesthetic function, and ideological significance within the development of Uzbek prose fiction. The study examines the core components of the plot—exposition, conflict, development of events, climax, and resolution—through close textual analysis.